A Systematic review of the factors that affect soccer players' short-passing ability-based on the Loughborough Soccer Passing Test - Bihan Wang; Bin Wan; Shu Chen; Yu Zhang; Xiaorong Bai; Wensheng Xiao; Changfa Tang; Bo Long (BMC, 2024)
Abstract Objective This study synthesizes evidence from the Loughborough Passing Test to evaluate the short-passing ability of soccer players and summarizes the reported variables that affect this ability to provide support for the development and improvement of short-passing abilities in soccer players. Methods In this systematic review using the PRISMA guidelines, a comprehensive search was conducted in Web of Science, PubMed, and EBSCOhost from inception to July 2023 to identify relevant articles from the accessible literature. Only studies that used the Loughborough test to assess athletes' short-passing ability were included. The quality of the included studies was independently assessed by two reviewers using the PEDro scale, and two authors independently completed the data extraction. Results Based on the type of intervention or influencing factor, ten studies investigated training, nine studies investigated fatigue, nine studies investigated supplement intake, and five studies investigated other factors. Conclusion Evidence indicates that fitness training, small-sided games training, and warm-up training have positive effects on athletes' short-passing ability, high-intensity special-position training and water intake have no discernible impact, mental and muscular exhaustion have a significantly negative effect, and the effect of nutritional ergogenic aid intake is not yet clear. Future research should examine more elements that can affect soccer players' short-passing ability. Trial registration https://inplasy.com/ ., identifier: INPLASY20237.